Parental effects driven by resource provisioning in Alternanthera philoxeroides—A simulation case study - Wang, Lan-Hui; Si, Jing; Luo, Fang-Li; Dong, Bi-Cheng; Yu, Fei-Hai (Frontiers in Plant Science, 2022)
Parental environmental effects can be a rapid and effective means for clonal plants in response to temporally or spatially varying environments. However, few studies have been conducted to quantitatively measure the ecological significance of parental effects. In this study, we developed a two-generation (parent-offspring) growth model to examine the parental effects of N conditions on individual performance and population growth of clonal offspring of the well-studied, clonal herb Alternanthera philoxeroides. We also attempted to explore the role of two key factors (i.e., survival rate and developmental stage of clonal offspring) in the consequence of parental effects. Our simulation results provided direct evidence that (1) there were significant non-linear correlations between the performance of parent plants and initial status of clonal offspring (i.e., initial mass and number of clonal offspring); (2) parental N effects on the summed performance of clonal offspring were content-dependent (i.e., there were significant interactions between parental and offspring N effects), while parental effects on the mean performance of offspring were independent of offspring conditions; (3) parental effects mainly occurred at the early development stage of clonal offspring, and then gradually declined at the late stage; (4) the context-dependent parental effects on the summed performance of clonal offspring gradually strengthened when the survival rate of offspring was maintained at a higher level. Overall, the mathematical models based on the experimental data may help researchers to not only deeply explore the ecological significance of parental environmental effects in clonal plants, but also to reveal the importance of potential factors that have been often neglected in empirical studies.